Sistem Rekomendasi Bantuan Rutilahu Kabupaten Sumedang Menggunakan Metode Multi Attribute Utility Theory - Syarifudin Yoga Pinasty; Tacbir Hendro Pudjiantoro; Fajri Rakhmat Umbara (Prosiding SISFOTEK, 2020)
The house is a place to live and shelter for humans as well as a place for daily activities and in Sumedang Regency there are still many houses that are categorized as uninhabitable house, because there are still people who are categorized as having uninhabitable houses, the government routinely provides assistance and due to limited funds owned by the Government as well as many people who submit requests for assistance,but the Government cannot provide assistance at the same time to all people who submit. The applicant for assistance must wait if not yet selected to get help, to get help, a selection of aid opinions must be made to make it right on target. Decision making related to the determination of the community who will receive assistance first, it will be carried out the construction of a system that aims to support a decision in the sense of a decision support system instead of replacing humans as decision makers in providing uninhabitable housing assistance, but can provide a picture or more knowledge towards humans for decision making,where the system development will be used by the Dinas Sosial Sumedang and using the Multi Attribute Utility Theory (MAUT) method and for this method that is calculating the normalization and weight that will be multiplied by the components needed so that the final result is a ranking order from the evaluation results.